Pengaruh Good Corporate Governance, Intensitas Modal Dan Koneksi Politik Terhadap Tax Avoidance - Jamilah, Siti; Sri Agustini (GLOBAL SCIENTS PUBLISHER, 2024)
This research aims to determine the influence of good corporate governance, capital intensity, and political connections on tax avoidance. The population of this research involves banking companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2023 period. The type of research applied is quantitative research with an associative approach. The data used in this research is secondary data. Samples were selected using a purposive sampling method, and from this method 140 data samples were obtained. The analytical method used is multiple linear regression with panel data, with data processing carried out using the Eviews 13 program. The results of this research show that good corporate governance, capital intensity and political connections simultaneously have a positive effect on tax avoidance. However, partially, the results show that good corporate governance as measured through the proxies of the independent board of commissioners and audit committee has no effect on tax avoidance. Furthermore, capital intensity and political connections partially have a positive effect on tax avoidance.